Refractive Status after Phacoemulsification with Biometry Done by Haigis and SRK-T Formulae in Myopic Patients (Journal of National Institute of Ophthalmology, 2023)
Background: Optimum refractive outcome is the key indicator for assessing the success of cataract surgery. Accurate biometric calculation of IOL is an important contributor of post-operative refractive status. There are several formulae for calculation of IOL power depending on axial length of eyes. Haigis is the formula of choice for calculating IOL power in myopic patients, whereas, SRK-T is a versatile formula irrespective of axial length. For IOL power calculation by Haigis formula needs expensive instrument. On the other hand, biometry by SRK-T formula can be done by less expensive and easily available instrument.Objective: To assess and compare post-operative refractive status after phacoemulsification where biometry done by Haigis and SRK-T formulae.Methods: This prospective observational study was conducted over 60 diagnosed patients of cataract with axial length more than 24 mm attending in the cataract clinic of NIO&H for phacoemulsification. Patients were selected based on specific selection criteria. Selected patients underwent detail ophthalmic and systemic examination as well as relevant investigation. Biometric calculation of IOL power was done by a single skilled technician by using Haigis formula (group A) in 30 patients and SRK-T formula (group B) in 30 patients. Visual acuity was assessed by LogMAR unit after 4 weeks of surgery and compared between two groups, p value ≤0.05 was considered as significant.Results: Mean age of the study subjects were 57.7±6.0 (SD) years in group A and 57.27±5.48 (SD) years in group B. In group A 14(46.7%) were male and 16(53.3%) were female and in group B 16(53.3%) were male and 14(46.7%) were female. Mean axial length was 25.05±0.45 (SD) mm in group A and 24.88±0.32 (SD) mm in group B. Mean IOL power was 18.23±0.76 (SD) diopter in group A and 18.23±0.65 (SD) diopter in group B. Post-operative mean visual acuity was 0.19±0.26 (SD) LogMAR unit in group A and 0.18 ±0.27 (SD) LogMAR unit in group B. Regarding post-operative refractive status of the study subjects, in group A, out of 30 patients 14(46.7%) were emmetropic, 7(23.3%) were myopic, 5(16.7%) were hypermetropic and the rest 4(13.3%) patients had astigmatism and in group B, out of 30 patients 16(53.3%) were emmetropic, 5(16.7%) were myopic, 4(13.3%) were hypermetropic and the rest 5(16.7%) patients had astigmatism.Conclusion: Quantitative assessment and statistical analysis shows there was no significant difference in post-operative refractive status and mean visual acuity between two groups.J.Natl.Inst.Ophthalmol.2023;6(1): 42-47